Conventional radiofrequency ablation of sphenopalatine ganglion for the treatment of cluster headache - Sudhindra Dharmavaram (Indian Journal of Pain, 2016)
Cluster headache is a primary neurovascular unilateral headache associated with autonomic symptoms. The sphenopalatine ganglion plays an important role in the pathogenesis of this disorder. Although medications are the first line of treatment, percutaneous, and surgical interventions have been proposed to treat cluster headache. An attractive option is the radiofrequency ablation of the sphenopalatine ganglion for the treatment of cluster headache due to its relative safety and simplicity compared with other procedures.